Variations in emergency care for severe pre-eclampsia in Uganda: a national evaluation studyAJOG Global Reports at a Glance - Annettee Nakimuli, MD, PhD; Jackline Akello, MD; Musa Sekikubo, MD, PhD; Sarah Nakubulwa, MD, PhD; Moses Adroma, MD; Rehema Nabuufu; Emmanuel Obuya; John Paul Bagala, MD; Andrew Twinamatsiko, MD; Hadijah Nakatudde; Patrica Pirio, MD; Grace Latigi; et al. (AJOG Global Reports)
Background: Worldwide, 70% of maternal deaths occur in Sub-Saharan Africa. Approximately 10% are attributable to hypertensive disorders of pregnancy, primarily complications of pre-eclampsia. Timely and effective care improves outcomes, but this is not consistently available, particularly in low-resource settings such as Uganda. Objectives: We conducted a national evaluation of the provision of prompt and safe care for women with severe pre-eclampsia across all regions of Uganda. We explored the wider health system-related factors, eg supply availability, facilities, and emergency training drills, that may affect the ability of healthcare facilities to deliver optimal pre-eclampsia care. Study design: A multidisciplinary research team carried out in-person, unannounced visits to maternity facilities across Uganda to assess the quality of care provided. Evaluations of facilities, staff interviews, and case notes reviews were performed. Results: 75 maternity facilities were included from all regions of Uganda. Of these, 25% were unable to provide correct emergency care for severe pre-eclampsia, and 21% were unable to consistently provide delivery or referral for eclamptic seizure within 12 hours. Factors strongly associated with not providing optimal pre-eclampsia care were lack of staff training, lack of readily available clinical protocols, lack of antenatal education, lack of close postnatal monitoring and care that was not always woman-centered. Conclusions: The key barriers associated with delayed or poor quality pre-eclampsia care across Uganda are potentially modifiable with strengthened clinical governance initiatives. Developing context-specific, standardized, national training and educational programmes could be effective in reducing rates of maternal and neonatal morbidity and mortality from pre-eclampsia.